URATE NEPHROPATHY’S CAUSES AND CLINIC LABORATORY MANIFESTATIONS IN CHILDHOOD PERIOD (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2024)
Urate nephropathy in children is based on increased production of uric acid and, as a result, an increase in its concentration in the released blood and urine. According to various authors, this violation is recorded in 3-17% of the examined people. Environmental factors, urbanization, nutritional patterns can lead to the spread of such disturbances in the purine exchange. Urate nephropathy often proceeds covertly and it is detected by chance. This pathology is diagnosed in the stage of nephrosclerosis with slowly progressing nitrogemia and pronounced arterial hypertension and in climatically unfavourable seasons of the year when adapted. Such variants of dysmetabolic nephropathies are known econephropathy [1].